En Masse Distalization As A Treatment Option In Correction Of Skeletal Class Ii Malocclusion. - MOHAN, AKSHAY; BABU, HARISH; BALAKRISHNAN, NIVETHIGAA (The journal of contemporary issues in business and government, 2021)
Treatment of skeletal Class II malocclusion in a growing patient will involve growth modification therapy using myofunctional appliances. In case of some patients non compliance Class II correctors may be used to correct discrepancies. Skeletal Class II malocclusion due to prognathic maxilla may require headgears for correction. The introduction of infra zygomatic screws and buccal shelf screws have broadened the scope of Class II correction in late adolescence and adults. Invariably patients with skeletal Class II malocclusions do not report to the orthodontists at a time when growth can be harnessed for correction of the skeletal malocclusion. In most of these cases camouflage treatment or orthognathic surgery were the options. Bone screws have now changed the scenario providing patients with the option of en masse distalisation not involving extractions or surgery. This study aims to evaluate the treatment options not involving growth modification chosen for patients with skeletal Class II malocclusion. Patient records were screened for skeletal Class II malocclusion, patients from the age group of 14 to 35 were chosen for the study. Patients undergoing treatment with myofunctional appliances and non compliance Class II correctors were eliminated from the study. A total of 80 patient records were obtained. Data on age, gender and treatment plan were tabulated. Samples were divided into three groups based on treatment plan. Group A (N= 50) represented camouflage treatment, Group B (N= 16) represented en masse distalisation and Group C (N= 14) represented orthognathic surgery. The association between age, gender and treatment plan was tested using Pearson’s test of independence. Results of the study showed that 62.5% of all patients in the study had undergone camouflage treatment with only 20% undergoing en masse distalisation. 17.5% of patients had undergone orthognathic surgery. It was observed that the age group of 20-24 years contributed to the maximum number of patients reporting for correction of Class II skeletal malocclusions. Pearson Chi-Square value of 2.843 and p-value of 0.241( p-value< 0.05 significant) showed that there was no association between gender and treatment plan chosen. Pearson’s Chi Square value of 18.09 and p value of 0.021 (p value < 0.05,statistically significant) showed an association between age and treatment plan chosen for the patient. From the results of the study it can be concluded that there was an association between age and treatment plan in correction of Class II malocclusion. En masse distalisation as a treatment option was predominantly chosen in late adolescence and young adults.